Privacy, Data Protection and Cybersecurity in Europe - Baumann, Max-Otto; Schünemann, Wolf J. (Springer, 2017)
This book offers a comparative perspective on data protection and cybersecurity in Europe. In light of the digital revolution and the implementation of social media applications and big data innovations, it analyzes threat perceptions regarding privacy and cyber security, and examines socio-political differences in the fundamental conceptions and narratives of privacy, and in data protection regimes, across various European countries. The first part of the book raises fundamental legal and ethical questions concerning data protection; the second analyses discourses on cybersecurity and data protection in various European countries; and the third part discusses EU regulations and norms intended to create harmonized data protection regimes
Keywords: Konferenzschrift; Privatsphäre; Internet; Datensicherung; Europa